Pre‐school children and marketing communications. (September 2016) - Preston, Christopher
Abstract: Within the context of an existing body of work regarding children and marketing communications, which largely places meaningful interaction with marketing communication as out with the ability of pre‐school children, research has been conducted upon parents of pre‐school children, nursery teachers and pre‐school children themselves within the environment of their nursery. Parents relate their experience that typically from the age of three their children recognize television advertising and have commenced retail interactions. Nursery teachers have noted that the children under their care personally interact within the context of brands, and the children themselves via their own verbalisations provide indications that in some cases at least 4‐year‐old children have an idea of advertising intent, and 3‐year‐old children typically are able to recognize advertising as being distinct from programme material.